Good habits gone bad: Explaining negative consequences associated with the use of mobile phones from a dual‐systems perspective. (24th February 2015) - Soror, Amr A.; Hammer, Bryan I.; Steelman, Zachary R.; Davis, Fred D.; Limayem, Moez M.; Tarafdar, Monideepa; Gupta, Ashish; Turel, Ofir
Abstract Information technology use is typically assumed to have positive effects for users, yet information technology use may also lead to negative consequences with various degrees of gravity. In the current work, we build on dual‐systems theories to investigate negative consequences associated with mobile phones use (MPU), defined as the extent to which the use of mobile phones is perceived to create problems in managing one's personal and social life. According to dual‐system theories, human behaviour is guided by two systems: reflexive (automatic) and reflective (control), which most of the time work in harmony. But when the two systems come into conflict, they will both complete to exert their influences over behaviour. Thus, we view the negative consequences associated with MPU as an outcome of the tug‐of‐war between the two systems influencing our day‐to‐day behaviours, where reflexive system is represented in our study by MPU habits and reflective system is represented by self‐regulation. We hypothesise that the influence of habit and self‐regulation on these negative consequences will be mediated through MPU. A partial least square analysis of 266 responses was used to validate and test our model. The study results generally support our model. The theoretical and practical implications of our study are discussed.